Evaluating the Gains of Using Stories in Medical Education–A Pilot Study Example - Gamsızkan, Zerrin; Sungur, Mehmet Ali; Günel, Mehmet Göktuğ (Bangladesh Journal of Medical Science, 2022)
Objectives: Medical education develops day by day with the effect of its unique dynamics, excessive information load and changing education approach depending on its professional characteristics.The aim of this study wasto determineeffects on the knowledge and attitude gains of story usage in education. Material and Methods: This is a training intervention study with a twenty-five study group and twenty-five control group students. A 20-question test was applied to the students before and after the study, including the topics of course. In addition, students were asked to provide feedback on the educational practice. Results and Dıscussion: According to the results of this study applied with twenty-five students study and control groups; in addition to theoretical lessons, reading and discussing patient stories covering lesson topics significantly increases students’ academic knowledge (p <0.001). 90.4% of the students stated that the study generally met their expectations, 95.2% of them wanted to take this kind of application in other education modules and 89.6% of them stated that the study contributed to their learning. Coclusions: Student-centered interactive education sessions increase students’ academic success in higher education. The student feedbacks we obtained in our study results have guided our future education interventions. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 694-701